PENINGKATAN LITERASI DAN NUMERASI SEKOLAH DASAR MELALUI FUN LITERACY ACTIVITY (FLA) BERBASIS GAME “ULTRASI” - Wahyuningtyas, Lutfi; Puspitasari, Yulia Dewi (Universitas Cenderawasih, 2024)
The purpose of this study was to improve literacy and numeracy outcomes through FUN LITERACY ACTIVITY (FLA) based on the snake and ladder literacy and numeracy game (Ultrasi) of grade V students at Elementary School 2 Getas. This type of research is Classroom Action Research (CAR). The CAR model used is the Stephen Kemmis & Mc. Taggart model which is implemented in 2 cycles. Data collection techniques in this study are observation, documentation and testing. Observations were carried out at each stage of implementation, and documentation and tests were taken using the Class Minimum Competency Assessment (AKM). Data analysis is presented in the form of tables and also graphs of research results. Based on the results of the study, it is known that through this snake and ladder game-based learning, students' literacy and numeracy learning outcomes can be increased. This is indicated by an increase and achievement of the KKM target value of more than or equal to 50 and a percentage of completion of more than or equal to 90%. Based on the results of the study, the completion of cycle I was 52.94% literacy and 35.29% numeracy and the completion in cycle II increased by 94.12% for literacy and numeracy. Based on the results of the research and discussion conducted, from the implementation of the action through 2 cycles, it can be concluded that the application of FLA in the form of a snake and ladder game is appropriately effective to be applied in learning activities because it can improve students' literacy and numeracy.